2010
DOI: 10.1136/ard.2009.123588
|View full text |Cite
|
Sign up to set email alerts
|

Association of variation in Fc  receptor 3B gene copy number with rheumatoid arthritis in Caucasian samples

Abstract: Objective-There is increasing evidence that variation in gene copy number (CN) influences clinical phenotype. The low-affinity Fcγ receptor 3B (FCGR3B) located in the FCGR gene cluster is a CN polymorphic gene involved in the recruitment to sites of inflammation and activation of polymorphonuclear neutrophils (PMNs). Given recent evidence that low FCGR3B CN is a risk factor for systemic but not organ-specific autoimmune disease and the potential importance of PMN in the pathophysiology of rheumatoid arthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 47 publications
7
73
1
Order By: Relevance
“…The quantitative PCR assay method we have used has been validated previously. 2 The use of an internal reference in the PCR removes variations due to amplification efficiency and experimental conditions that can occur when test and reference genes are measured in separate wells. Cases and controls were also assayed concurrently, and a-posteriori assignment of CN rather than arbitrary rounding of non-integer values was done to minimise batch effects and systematic errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative PCR assay method we have used has been validated previously. 2 The use of an internal reference in the PCR removes variations due to amplification efficiency and experimental conditions that can occur when test and reference genes are measured in separate wells. Cases and controls were also assayed concurrently, and a-posteriori assignment of CN rather than arbitrary rounding of non-integer values was done to minimise batch effects and systematic errors.…”
Section: Discussionmentioning
confidence: 99%
“…2 The 1000 Genomes project has recently identified two SNPs at these 3 0 positions (rs115802971 and rs115130696) in individuals of Yoruban descent in which the minor allele corresponds to the FCGR3A sequence. Although an individual carrying these minor alleles would be falsely determined to have a deletion, the allele frequencies in Caucasian populations are very low, with the minor allele of these SNPs being observed in only one of the first 380 Caucasians sequenced in the 1000 Genomes project.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] However, most studies have not evaluated the contribution to this complex disorder of other forms of genetic variation, such as structural variations, mainly in the form of CNVs. 15 Indeed, CNVs have recently been shown to have an important role in complex disease phenotypes as psoriasis, 30 rheumatoid arthritis 31 and systemic lupus erythematosus. 32 Similarly, a copy number polymorphism including FCGR3 leads to a predisposition to glomerulonephritis in rats and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional roles of these genes in the development of immune system disorders and breast cancer are well documented (Howard et al, 1998;Hannigan et al, 2001;Fan et al, 2006;Cheng et al, 2009;McKinney et al, 2010), whether or not they contribute to increased BC risk in populations of non-European descent has not been investigated. In the present study, we investigated the expression of LSP1, HRAS, SIRT3, AP2A2 and SCUBE2 in Iranian BC patients and healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Hannigan et al reported that reduced chemotactic responses of LSP1 neutrophils are associated with discontinuous primary actin-rich cortexes and large abnormal membrane protrusions (Howard et al, 1998). Overexpression of LSP1 causes morphologic and motile abnormalities characteristic of the NAD 47/89 phenotype (McKinney et al, 2010).…”
Section: Introductionmentioning
confidence: 99%